Análisis de la gestión financiera en el presupuesto del GAD parroquial Caracol, periodo 2022 -2023. - Fonseca Mosquera, Katherine Genessi (2025)
This case study was carried out in the Decentralized Autonomous Government of the Parish of Caracol, where challenges in budget management were identified, which influences the implementation of projects. Considering that financial management is a key tool that will guarantee the sustainable development of the community. Therefore, the objective of this research is to carry out an analysis of the financial management of the budget of the Caracol Parish GAD in the periods 2022-2023, through the budgetary schedules, in order to identify factors that influenced the execution of the budget, as well as its alignment with the needs and priorities of the parish community. Therefore, the implementation of the research line "Financial, Administrative, Audit and Control Management" and the Subline "Audit and Control" was essential. In addition, the mixed methodology was implemented, which includes qualitative and quantitative approaches to examine the execution of the budget in the aforementioned periods. Likewise, the descriptive and explanatory type of research was used; in addition, the deductive method and documentary analysis were used, and an interview was used as a technique for collecting information. This was crucial for establishing relevant conclusions and recommendations that would contribute to the correct administrative management of the Parish GAD.